The Effect of Employee Engagement on Employee Performance in Ghana's MSMEs Sector During Covid-19: The Moderating Role of Job Resources - Daniel Nkansah; Raymond Gyimah; James Kwasi Annan; Daniel Agyemfour-Agyemang Sarpong (Journal of Social Science, 2023)
Micro, small and medium enterprises (MSMEs) across the globe have been the major victims of the COVID-19 pandemic, which has plunged the business world into a serious crisis. However, Employee Engagement (EE) has been labeled as an essential nutrient that organizations need in order to survive in these turbulent times. This study was to examine the effect of EE on Employee Performance during the COVID-19 pandemic and how this relationship is moderated by job demands. The study used a sample size of 395 respondents who were chosen from a variety of MSMEs via a convenience sampling method. The study used a survey questionnaire approach as the main method for collecting primary data. The result of the correlation analysis showed that there was a significant relationship between EE and employee performance. It was revealed that job resources moderated the relationship between EE and employee performance. Finally, the result showed that job resources had a significant effect on EE. Thus, it can be concluded that, in the face of COVID-19, EE is a significant predictor of the performance of employees in the MSMEs sector.